2009
DOI: 10.1105/tpc.108.064071
|View full text |Cite
|
Sign up to set email alerts
|

Tendril-lessRegulates Tendril Formation in Pea Leaves  

Abstract: Tendrils are contact-sensitive, filamentous organs that permit climbing plants to tether to their taller neighbors. Tendrilled legume species are grown as field crops, where the tendrils contribute to the physical support of the crop prior to harvest. The homeotic tendril-less (tl) mutation in garden pea (Pisum sativum), identified almost a century ago, transforms tendrils into leaflets. In this study, we used a systematic marker screen of fast neutron-generated tl deletion mutants to identify Tl as a Class I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 32 publications
1
131
0
1
Order By: Relevance
“…In addition to STF, LAM1, MAW, NS1, and NS2, which are WOX genes, class I HD-ZIP genes have been reported to control tendril and bract morphogenesis without necessarily disrupting polarity. For example, the tendril-less (tl) mutation in pea revealed that tendrils are modified leaves where lamina outgrowth is inhibited by repressive function of TL (Hofer et al, 2009), and a related gene in Arabidopsis, LATE MERISTEM IDENTITY1 (LMI1), is required for suppression of bract formation (Saddic et al, 2006). It remains to be shown if class I HD-ZIP genes target or interact with WOX genes in leaf primordia.…”
Section: Stf Controls Blade Outgrowth At the Adaxial-abaxial Boundarymentioning
confidence: 99%
“…In addition to STF, LAM1, MAW, NS1, and NS2, which are WOX genes, class I HD-ZIP genes have been reported to control tendril and bract morphogenesis without necessarily disrupting polarity. For example, the tendril-less (tl) mutation in pea revealed that tendrils are modified leaves where lamina outgrowth is inhibited by repressive function of TL (Hofer et al, 2009), and a related gene in Arabidopsis, LATE MERISTEM IDENTITY1 (LMI1), is required for suppression of bract formation (Saddic et al, 2006). It remains to be shown if class I HD-ZIP genes target or interact with WOX genes in leaf primordia.…”
Section: Stf Controls Blade Outgrowth At the Adaxial-abaxial Boundarymentioning
confidence: 99%
“…1 compost with 30% extra grit. DNA was prepared from leaves according to Vershinin et al (2003), and RNA was prepared from flowers according to Hofer et al (2009).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The garden pea is in some senses the founding model for genetics, through Mendel's work in 1866. Pea has been further developed as a model for development traits such as compound leaf form (Tattersall et al, 2005), tendril formation (Hofer et al, 2009), transposon evolution (Jing et al, 2005), defense responses (Gao et al, 2004), starch and sugar synthesis (Barratt et al, 2001), and hormonal control of shoot branching (Beveridge et al, 2009). Common bean has been used to characterize the molecular basis of photoperiod sensitivity and determinacy (Kwak et al, 2008).…”
Section: Many Models In the Legumesmentioning
confidence: 99%